Intersectional Reading, Social Justice & Literary Activism (INTERACT) - Harinen, Kaiju (SAGE Publications, Ltd., 2025)
Kaiju Harinen, PhD, postdoctoral researcher, University of Turku, discusses the INTERACT project on intersectional reading, social justice, and literary activism, including research methods used, data collection, and historical power dynamics.